Blood glucose response to kratom tea (Mitragyna speciosa Korth.) - Fadly Dzul (BIO Web of Conferences)
Background: Kratoms are traditionally used in Borneo to manage diabetes by chewing, smoking, or brewing the leaves as tea. Studying its effects on blood glucose is crucial for validating its therapeutic potential. Objective: This study evaluated the blood glucose response to kratom tea from West Kalimantan, Indonesia. Methods: This evaluation was executed using an experimental design with ten subjects, which included pure standard glucose in week 1 and standard glucose mixed with 1% kratom tea in week 2, with a 1-week wash-out period. Results: Postprandial blood glucose levels were measured over 2 hours. Results showed a higher increase in blood glucose levels in the pure glucose group (AUC: 579.98±27.15 mm²) compared to the kratom tea group (AUC: 493.30±24.27 mm²), with significant differences (p=0.01). Conclusion: Kratom tea significantly inhibited the increase in blood glucose level after meals.